Improvement of microstructure of bovine hydroxyapatite (BHA) by doping with calcium fluoride - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
Composites of calcinated bovine bone derived hydroxyapatite (BHA) doped 0.5 and 1 wt% CaF2 were prepared by sintering. The production of BHA from natural sources is preferred due to money and time saving reasons. Scanning electron microscopy (SEM) and X-ray diffraction analysis together with measurements of density and compression strength were carried out in the produced samples. The experimental results indicated that compression strength of the composites increase when sintering temperature increases. The best compression strength was achieved after sintering at 1200 degrees C for 0.5% CaF2 addition. The results are in agreement with densification measurements and microstructure analysis. With regards to the amount of CaF2, the results indicate that small additions of F, lower than 0.5%, can further improve the mechanical properties of HA.
Keywords: hydroxyapatite; calcium fluoride; sintering; microstructure; mechanical properties; MECHANICAL-PROPERTIES; SINTERED HYDROXYFLUORAPATITES; COMPOSITES